Engineering Eden: Does Earthly Pursuit of Eternal Life Threaten the Future of Religion?. Issue 2 (3rd April 2019) - Kostick, Kristin; Fowler, Leah; Scott, Christopher
ABSTRACT: The eternal life promised by many religions is mirrored by the drastically longer lifespans proposed by radical life extension (RLE) and transhumanism (H+). RLE and H+ represent extreme contingents of longevity research among the broader scientific initiatives to extend the length and quality of human life. In striving toward literal immortality, these movements offer an "alternative" to the spiritual eternity that functions as a religious solution to fear of death and loss. In this article, we probe the question of whether a radically extended—even eternal—life through advancements in biotechnology could replace religion as a means of managing this terror of death.